Limonium poimenum (Plumbaginaceae), a new chasmophyte species from Sicily - Ilardi, Vincenzo; Brullo, Salvatore; Cusimano, Dario; Galdo, Gianpietro Giusso Del (Phytotaxa, 2014)
Limonium poimenum is here proposed as a new species for Science. It is a very peculiar and extremely localized species, growing on a calcareous mountain of NW Sicily (southern Italy), where it grows on rupestrian places together with many other rare chasmophytic endemics. Iconography, morphological features, ecology and conservation status are provided, as well as a morphological comparison with L. todaroanum.